ASSESSMENT OF THE SENSITIVITY OF NEW CRITERIA FOR SYSTEMIC SCLEROSIS IN RUSSIAN PATIENT POPULATION - O. A. Koneva; O. B. Ovsyannikova; M. N. Starovoitova; E. O. Cheremukhina; E. N. Aleksandrova; L. P. Ananyeva (Научно-практическая ревматология, 2015)
Systemic sclerosis (SS) is a progressive connective tissue disease, the prognosis of which largely depends on the time of adequate therapy initiation. Low sensitivity of the 1980 American College of Rheumatology (ACR) SS classification criteria for identifying patients with early stage of the disease, and with its limited form in particular, has necessitated revision of existing SS diagnostic standards and elaboration of more sensitive criteria that allow to establish the diagnosis when the first sign of the disease appear.Objective: to compare the sensitivity of the novel SS criteria of ACR and European League against Rheumatism (ACR/EULAR) 2013 and the 1980 ACR criteria in different stages of the disease.Subjects and methods. The investigation enrolled 302 patients who had been diagnosed by experts as having SS and followed up at the V.A. Nasonova Research Institute of Rheumatology in 2007–2013. The patients’ mean age was 49±13 years (18 to 80 years); male to female ratio – 1:9 (31 and 271), that of patients with diffuse and limited SS – 1:2 (105 and 197); mean duration of the disease from the first non-Raynaud’s syndrome was 8.2±7.0 years (6 months to 36 years). Physical examination, nailfold capillaroscopy, chest radiography or computed tomography, echocardiography for the determination of pulmonary artery systolic pressure and SS-specific antibodies evaluation were performed.Results. 273 (90%) patients fulfilled the novel ACR/EULAR 2013 SS criteria. 76 (25%) patients had skin thickening above the metacarpophalangeal (MPC) joints in both hands; 263 (87%) – finger skin thickening [70 (23%) – finger swelling, 192 (64%) – thickening of all fingers distal to the MPC joints], 141 (47%) – digital ischemia [79 (26%) – digital pitting scars, 20 (7%) – digital ulcers, 42 (14%) – digital pitting scars and ulcers], 134 (44%) – telangiectasias, 276 (91%) – capillaroscopic changes, 225 (78%) – pulmonary hypertension (PH) or interstitial lung disease (ILD) [15 (5%) – PH 185 (61%) – ILD, 35 (12%) – ILD and PH], 301 (99%) – Raynaud’s phenomenon, and 185 (61%) – SS autoantibodies [138 (46%) – anti-Scl-70 antibodies (a-Scl-70), 42 (14%) – anti-centromere antibodies (ACA), 5 (1.7%) – ACA and a-Scl-70]. 216 (72%) patients fulfilled 1980 ACR SS criteria, and all of them met the novel criteria. With the latter, SS could be additionally diagnosed in 57 more (18%) patients.Conclusion. The 2013 ACR/EULAR SS classification criteria have much higher sensitivity than the 1980 ACR criteria. The sensitivity of the novel criteria remained at the level of 90% in all, including the earliest, stages of the disease while the ACR criteria allowed to confirm diagnosis of SS in only half of patients with a disease duration of less than 1 year.